The Concept of Speaking Fluency - Norpoʻlatova Nozima Yusufxon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract : Speaking fluency is a crucial aspect of language competence, encompassing the ability to produce speech smoothly, accurately, and appropriately in real time. According to Skehan (1996), fluency is not merely about speaking quickly; it also involves smoothness, automaticity, coherence, and the ability to manage conversation effectively. For EFL learners, developing fluency is often more challenging than learning grammar or vocabulary because it requires integrating multiple skills simultaneously, including lexical retrieval, sentence construction, pronunciation, and pragmatic awareness.